Genomic analysis of distinct bleaching tolerances among cryptic coral species. Issue 1960 (13th October 2021) - Rose, Noah H.; Bay, Rachael A.; Morikawa, Megan K.; Thomas, Luke; Sheets, Elizabeth A.; Palumbi, Stephen R.
Abstract : Reef-building coral species are experiencing an unprecedented decline owing to increasing frequency and intensity of marine heatwaves and associated bleaching-induced mortality. Closely related species from the Acropora hyacinthus species complex differ in heat tolerance and in their association with heat-tolerant symbionts. We used low-coverage full genome sequencing of 114 colonies monitored across the 2015 bleaching event in American Samoa to determine the genetic differences among four cryptic species (termed HA, HC, HD and HE) that have diverged in these species traits. Cryptic species differed strongly at thousands of single nucleotide polymorphisms across the genome which are enriched for amino acid changes in the bleaching-resistant species HE. In addition, HE also showed two particularly divergent regions with strong signals of differentiation. One approximately 220 kb locus, HES1, contained the majority of fixed differences in HE. A second locus, HES2, was fixed in HE but polymorphic in the other cryptic species. Surprisingly, non-HE individuals with HE-like haplotypes at HES2 were more likely to bleach. At both loci, HE showed particular sequence similarity to a congener, Acropora millepora . Overall, resilience to bleaching during the third global bleaching event was strongly structured by host cryptic species, buoyed by differences in symbiont associations between these species.